1993
DOI: 10.1111/j.1432-1033.1993.tb17600.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical, immunological and ultrastructural characterization of aggregation substances encoded by Enterococcus faeclis sex‐pheromone plasmids

Abstract: The sex-pheromone system of Enterococcus faecalis can be viewed as a unique and highly efficient plasmid-collection mechanism. The contact needed for transfer of the conjugative sexpheromone plasmids is mediated by an adhesin, called aggregation substance, which is encoded by these plasmids. We show here that for 17 of the 18 sex-pheromone plasmids (pAM373 being the exception) described to date, their adhesins are immunologically related to each other. In each case, we observed the presence of an N-terminal fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
25
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 26 publications
3
25
0
Order By: Relevance
“…These authors also noted, however, proteins of 130, 153 and 157 kDa after induction. Meanwhile we demonstrated that these higher-molecular-mass proteins are different forms of ASAl migrating differently in SDSPAGE (Hirt et al, 1993) and that the low-molecular-mass proteins to OrjjL represent an N-terminal fragment of the adhesin (depending on the extraction procedures for ASAl different amounts of the mature 137-kDa adhesin or its prominent 74/78-kDa Nterminal fragment are isolated). The situation was also complicated (but see below for explanation) by the fact that the pPD1-encoded gene pd78 does not show similarity to asal, and its gene product PD78 was reported to be important for cell aggregation and mating (Nakayama et al, 1990).…”
Section: Functions Of the Various Padl-encoded Genesmentioning
confidence: 87%
See 1 more Smart Citation
“…These authors also noted, however, proteins of 130, 153 and 157 kDa after induction. Meanwhile we demonstrated that these higher-molecular-mass proteins are different forms of ASAl migrating differently in SDSPAGE (Hirt et al, 1993) and that the low-molecular-mass proteins to OrjjL represent an N-terminal fragment of the adhesin (depending on the extraction procedures for ASAl different amounts of the mature 137-kDa adhesin or its prominent 74/78-kDa Nterminal fragment are isolated). The situation was also complicated (but see below for explanation) by the fact that the pPD1-encoded gene pd78 does not show similarity to asal, and its gene product PD78 was reported to be important for cell aggregation and mating (Nakayama et al, 1990).…”
Section: Functions Of the Various Padl-encoded Genesmentioning
confidence: 87%
“…(d) The structural gene for aggregation substance is present in all plasmids except pAM373 ; in addition, polyclonal antibodies against ASAl react with induced cells carrying the various sex pheromone plamids, again with pAM373 as an exception. (Details of these data can be found in Galli and Wirth, 1991;Weidlich et al, 1992;Hirt et al, 1993).…”
Section: Dna Hybridizations and Sequence Comparisonsmentioning
confidence: 99%
“…AS of E. faecalis is highly conserved among sex pheromone plasmids (25) and was assumed to be a contributor to virulence of this important nosocomial pathogen after sequencing studies revealed the presence of two RGD motifs encoded in the AS protein (20,21,27). Kreft and coworkers demonstrated increased adhesion of AS-expressing cells to cultured renal tubular cells (28), which could be inhibited somewhat by the addition of RGD-containing peptides.…”
mentioning
confidence: 99%
“…Secondary structural analysis yields little information with the exception of a predicted alpha-helix domain from amino acids 200 to 280 (36). Isolation of AS yields both a full-length version of the protein (137 kDa) and a specific, 78-kDa, N-terminal cleavage product (9). Scanning electron microscopy of Asa1 on the cell surface suggests that the N terminus of the protein is more exposed than the C terminus (9).…”
mentioning
confidence: 99%
“…Isolation of AS yields both a full-length version of the protein (137 kDa) and a specific, 78-kDa, N-terminal cleavage product (9). Scanning electron microscopy of Asa1 on the cell surface suggests that the N terminus of the protein is more exposed than the C terminus (9). Finally, the only structural analysis of AS done to date found that an aggregation domain of Asa1 from amino acids 525 to 617 (of the mature protein with the signal sequence removed) exists and that the C terminus plays no essential role in aggregation (20).…”
mentioning
confidence: 99%